THE EFFECT OF LEADERSHIP STYLE ON WORK MOTIVATION OF PASIMARANNU VILLAGE, SINJAI TIMUR DISTRICT, SINJAI REGENCY - Erfiani Erfiani; Anwar Ramli; Muh. Ichwan Musa; M. Ikhwan Maulana Haeruddin; Muhammad Ilham Wardhana Haeruddin (Cross-Border Journal of Business Management, 2022)
This study aims to determine the positive and significant influence of leadership style on work motivation of the Passimarannu Village apparatus, East Sinjai District, Sinjai Regency. The population and sample in this study were 30 people. Data collection is carried out by means of questionnaires and documentation. The analytical method used is Un Normality. Multicollinearterras and Un Heteroscedasticity tests were tested with Multiple Regression Analysis. The results of the study after the data was processed with IBM SPSS 25 it was found that it has a positive and significant influence on leadership gava on work motivation of the Passimarannu Village apparatus, East Sinjai District, Siniai Regency, it can be concluded that the gava leadership has an influence on employee work motivation at the Pasimarannu Village Office, Sinjax Timar District, Singar Regency